2022
DOI: 10.1155/2022/2067632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MMP-9 Genetic Polymorphism and Concentration on the Development of Coronary Artery Disease in Ukrainian Population

Abstract: Coronary artery disease (CAD) is one of the leading causes of death in Europe. It is known that atherosclerosis is the primary risk factor of CAD development. MMP-9 is involved in all stages of atherosclerosis and thus may contribute to CAD emergence. To investigate the influence of MMP-9 on the (CAD) development 25 patients with intact coronary arteries (CA), 40 patients with acute coronary syndrome (ACS), and 63 patients with chronic coronary syndrome (CCS) were enrolled in the study. Real-time PCR was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[13][14][15] Even though MMP-9 belongs to the family of metalloproteinase and is considered to be widely studied, researchers continue to study the role of this enzyme in atherosclerosis, ACS, MI and other cardiovascular diseases (CVD). [16][17][18][19] The most recent studies continue to investigate the MMP-9 role as a player in pathways of myocardial injury and its place in the field of prognostic markers in cardiovascular pathology. [20][21][22][23] And its role is under investigation not only in cardiovascular pathology, but also in chronic Chagas disease, ocular pathology, ischemic stroke, in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Even though MMP-9 belongs to the family of metalloproteinase and is considered to be widely studied, researchers continue to study the role of this enzyme in atherosclerosis, ACS, MI and other cardiovascular diseases (CVD). [16][17][18][19] The most recent studies continue to investigate the MMP-9 role as a player in pathways of myocardial injury and its place in the field of prognostic markers in cardiovascular pathology. [20][21][22][23] And its role is under investigation not only in cardiovascular pathology, but also in chronic Chagas disease, ocular pathology, ischemic stroke, in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers found that HSP27 expression was increased in single nucleated cells of human peripheral blood and significantly correlated with the severity of CAD, rendering it a potential prognostic marker (29). Matrix metalloproteinase-9 (MMP9), an important member of MMP, is involved in the whole process of AS and high MMP9 expression is associated with plaque instability (30,31). In a subsequent analysis, these genes were found to be positively or negatively correlated with some immune cells, suggesting that the genes and the immune microenvironment influence each other, but the exact mechanism is unknown.…”
Section: Nk Cells Activated Mast Cells Resting T Cells Gamma Delta Ne...mentioning
confidence: 99%
“… 5 , 6 Furthermore, MMP-9 polymorphism, MMP-9/TIMP-1 imbalance and ECM turnover are considered the leading cause of coronary plaque instability and mortality. 8 - 10 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Furthermore, MMP-9 polymorphism, MMP-9/TIMP-1 imbalance and ECM turnover are considered the leading cause of coronary plaque instability and mortality. [8][9][10] The precise interaction between pro-inflammatory cytokines and MMP-9 is significant in atherosclerotic plaque formation and vascular lesions. 11,12 Several pro-…”
mentioning
confidence: 99%
See 1 more Smart Citation